2022
DOI: 10.1155/2022/7785714
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Study on the Central Mechanism of Penehyclidine Hydrochloride against Relapse Behavior in Morphine-Dependent Rats

Abstract: Objective. This article is mainly to study the central mechanism of penehyclidine hydrochloride against relapse behavior in morphine-dependent rats. Methods. The rats were randomly divided into the blank control group (k), PHC low-dose group (LP according to a body weight of 0.22 mg/kg), middle-dose group (MP according to a body weight of 0.55 mg/kg), high-dose group (HP according to a body weight of 1.38 mg/kg), and administration group, with 40 rats in each group. Each group was randomly divided into 5 subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%